Social Economy, Social Entrepreneurship and Social Innovation in the Labour (Re-)Integration of Vulnerable Social Groups: Preliminary Findings from a Qualitative Study - Kostas, Antonios (Κοινωνική Πολιτική, 2026)
This research note presents, in a highly condensed format, the methodology and preliminary findings of the research activity “Social Economy, Social Entrepreneurship, and Social Innovation in the labour (re-)integration of vulnerable social groups”. Centered on the Limited Liability Social Cooperative (LLSC) of Kavala, the study employs qualitative focus groups to investigate how a Work Integration Social Enterprise, specifically a Social Integration Cooperative Enterprise for Vulnerable Groups, operationalises labour inclusion in conjunction with therapeutic support. Preliminary findings identify a resilient hybrid model that effectively synthesises therapeutic objectives with labour-market activity, bridging systemic welfare gaps, driving sustainable labour integration, and fostering clinical and therapeutic success. The analysis contributes toward fostering a strategic “Social Policy Roadmap” for sustainable labour (re-)integration and socio-economic autonomy, grounded in the principles of Social Economy, Social Entrepreneurship, and Social Innovation.